2020
DOI: 10.21203/rs.3.rs-134425/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GWENA: Gene Co-expression Networks Analysis and Extended Modules Characterization in a Single Bioconductor Package

Abstract: Background: Network-based analysis of gene expression through co-expression networks can be used to investigate modular interactions occurring between genes toward different biological functions. An extended description of the network modules is therefore a critical step to understand the underlying processes contributing to a disease or a phenotype. Biological integration, topology study and conditions comparison (e.g. wild vs mutant) are the main methods to do so, but to date no tool combines them all into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Hub genes are characterized by being genes whose degree value is higher than the average of the threshold network degree value 84 . Many studies have shown that the relationship between connectivity and node significance carries important biological information 47 .…”
Section: Correlation Network and Identification Of Hub Genesmentioning
confidence: 99%
“…Hub genes are characterized by being genes whose degree value is higher than the average of the threshold network degree value 84 . Many studies have shown that the relationship between connectivity and node significance carries important biological information 47 .…”
Section: Correlation Network and Identification Of Hub Genesmentioning
confidence: 99%
“…The hub genes are characterized by being genes whose degree value is higher than the average of the threshold network degree value 43 . Many studies have shown that the relationship between connectivity and node signi cance carries important biological information 49 .…”
Section: Correlation Network and Identi Cation Of Hub Genesmentioning
confidence: 99%
“…Genes expressed in less than half of the samples were removed and strong outlier samples were removed in order to get a better fit to a scale-free topology. We tested two network construction pipelines: 1) The pipeline proposed by the authors of Gene Whole co-Expression Network Analysis (GWENA) (Lemoine et al, 2021), which consists of applying the variance stabilizing transformation (VST) from DESeq2 (Love et al, 2014) and using spearman correlations, and 2) counts adjusted with trimmed mean of M-values (TMM) factors followed by asinh transformation, Pearson correlations and network transformation by context likelihood of relatedness (CLR) (Johnson and Krishnan, 2022). Before creating the correlation matrices, normalised gene expression was corrected for covariates with limma's removeBatchEffect function (Ritchie et al, 2015) to account for the effect of the interaction of tissue type and BioProject ID, as those were the main drivers of the groupings seen in the exploratory analysis.…”
Section: Co-expression Analysesmentioning
confidence: 99%
“…The 30% less variable genes were removed for network construction. Co-expression networks were constructed with GWENA (Lemoine et al, 2021) R package, which implements the Weighted Correlation Network Analysis (WGCNA) (Langfelder and Horvath, 2008) R package.…”
Section: Co-expression Analysesmentioning
confidence: 99%
See 1 more Smart Citation